Structuring biofilm communities living in pesticide contaminated water. Issue 5 (May 2020) - Lima, Jhenifer Yonara; Moreira, Cassiano; Nunes Freitas, Paloma Nathane; Olchanheski, Luiz Ricardo; Veiga Pileggi, Sonia Alvim; Etto, Rafael Mazer; Staley, Christopher; Sadowsky, Michael Jay; Pileggi, Marcos
Abstract: The wide use of pesticides in agriculture expose microbiota to stressful conditions that require the development of survival strategies. The bacterial response to many pollutants has not been elucidated in detail, as well as the evolutionary processes that occur to build adapted communities. The purpose of this study was to evaluate the bacterial population structure and adaptation strategies in planktonic and biofilm communities in limited environments, as tanks containing water used for washing herbicide containers. This biodiversity, with high percentage of nonculturable microorganisms, was characterized based on habitat and abiotic parameters using molecular and bioinformatics tools. According to water and wastewater standards, the physicochemical conditions of the tank water were inadequate for survival of the identified bacteria, which had to develop survival strategies in this hostile environment. The biodiversity decreased in the transition from planktonic to biofilm samples, indicating a possible association between genetic drift and selection of individuals that survive under stressful conditions, such as heating in water and the presence of chlorine, fluorine and agrochemicals over a six-month period. The abundance of Enterobacter, Acinetobacter and Pseudomonas in biofilms from water tanks was linked to essential processes, deduced from the genes attributed to these taxonomic units, and related to biofilm formation, structure and membrane transport, quorum sensing and xenobiotic degradation. These characteristics were randomly combined and fixed in the biofilm community. Thus, communities of biofilm bacteria obtained under these environmental conditions serve as interesting models for studying herbicide biodegradation kinetics and the prospects of consortia suitable for use in bioremediation in reservoirs containing herbicide-contaminated wastewater, as biofilters containing biofilm communities capable of degrading herbicides. Abstract : Microbiology; Adaptation; Biodiversity; Bacteria; Microbial genomics; Biofilms; Microbial biotechnology; Environmental microbiology; Xenobiotics; Herbicide biodegradation; Bacterial diversity; Bioremediation; Bacterial adaptation.